2022
DOI: 10.1186/s12885-022-09743-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor and peritumor radiomics analysis based on contrast-enhanced CT for predicting early and late recurrence of hepatocellular carcinoma after liver resection

Abstract: Background In China, liver resection has been proven to be one of the most important strategies for hepatocellular carcinoma patients, but the recurrence rate is high. This study sought to investigate the prognostic value of pretreatment tumor and peritumor contrast-enhanced CT radiomics features for early and late recurrence of BCLC stage 0-B hepatocellular carcinoma after liver resection. Methods This study involved 329 hepatocellular carcinoma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previous studies have reported that radiomics analysis of intratumoral combined 3 mm, 5 mm, and 10 mm peritumoral regions can provide valuable information for prognosis prediction in HCC [ 18 , 19 , 30 , 39 , 40 ]. In addition, according to the practice guidelines for the pathological diagnosis of primary liver cancer (2015 update) [ 41 ], the liver tissues within 10 mm surrounding the tumor are defined as the adjacent areas around the cancer, where the probability of MVI is high.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that radiomics analysis of intratumoral combined 3 mm, 5 mm, and 10 mm peritumoral regions can provide valuable information for prognosis prediction in HCC [ 18 , 19 , 30 , 39 , 40 ]. In addition, according to the practice guidelines for the pathological diagnosis of primary liver cancer (2015 update) [ 41 ], the liver tissues within 10 mm surrounding the tumor are defined as the adjacent areas around the cancer, where the probability of MVI is high.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of radiomics, Previous studies have found that peritumoral radiomics is more valuable in assessing tumor heterogeneity ( 28 , 29 ). However, existing radiomic studies are controversial with regard to the range of peritumoral ROIs for predicting HCC recurrence ( 20 , 30 , 31 ). Therefore, we constructed multiple models with different ranges of ROI radiomics to explore the highly aggressive peritumoral region.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the combination of AFP and radiomic characteristics can effectively predict GPC3 expression (respective AUC values for the training and validation groups: 0.926 and 0.914). In this research, four features were screened out from 107 imaging features to construct a whole-tumor model, and a whole-tumor and peritumoral model was constructed using the same method considering micrometastasis and microinfiltration of immune-associated cells of the surrounding area of HCC, which was used less frequently in previous studies ( 21 , 22 ). Two logistic regression models were built to predict the level of RRM2 expression.…”
Section: Discussionmentioning
confidence: 99%